Synthesis and antiviral activities of hexadecyloxypropyl prodrugs of acyclic nucleoside phosphonates containing guanine or hypoxanthine and a (S)-HPMP or PEE acyclic moiety - Tichý, Tomáš; Andrei, Graciela; Snoeck, Robert; Balzarini, Jan; Dračínský, Martin; Krečmerová, Marcela (European journal of medicinal chemistry, 2012)
Hexadecyloxypropyl esters of acyclic nucleoside phosphonates containing guanine (G) or hypoxanthine (Hx) and a (S)-[3-hydroxy-2-(phosphonomethoxy)propyl] [(S)-HPMP] or 2-(2-phosphonoethoxy)ethyl (PEE) acyclic moiety have been prepared. The activity of the prodrugs was evaluated in vitro against different virus families. Whereas ester derivatives of PEEHx and (S)-HPMPHx were antivirally inactive, monoesters of PEEG, and mono- and diesters of (S)-HPMPG showed pronounced antiviral activity against vaccinia virus and/or herpesviruses. Monoesters of (S)-HPMPG emerged as the most potent and selective derivatives against these DNA viruses. None of the compounds were inhibitory against RNA viruses and retroviruses.
Keywords: Phosphorous Acids; Antiviral Agents; buněčné linie; lidé; vztahy mezi strukturou a aktivitou; Nucleosides; hypoxanthiny; prekurzory léčiv; techniky syntetické chemie; Prodrugs; Cell Line; kyseliny fosforité; guanin; hypoxanthin; nukleosidy; Humans; Guanine; organofosfonáty; Structure-Activity Relationship; antivirové látky; DNA viry; Chemistry Techniques, Synthetic; zvířata; DNA Viruses; Organophosphonates; Hypoxanthine; Animals; Hypoxanthines